Multi-Omics in Biomedical Sciences and Environmental Sustainability: Applications and Recent Advances - Kesheri, Minu; Kanchan, Swarna; Häder, Donat-Peter; Sinha, Rajeshwar P. (Springer Science+Business Media, 2025)
This book offers a comprehensive exploration of the cutting-edge multi-omics technologies that are revolutionizing research across biomedical sciences and environmental sustainability. It addresses the urgent need for interdisciplinary research by integrating multi-omics approaches with bioinformatics and artificial intelligence. The book explores evolution of traditional omics technologies into comprehensive multi-omics strategies that synergize data output through advanced computational tools. It covers diverse topics such as health and disease mechanisms, drug discovery innovations, COVID-19 responses, cancer treatment personalization, neuroscience insights into brain disorders, cyanobacterial natural compounds' potential for biofuel production, lichen symbiosis studies, and more. This volume integrates genomics, proteomics, metabolomics, and more with bioinformatics, machine learning, and artificial intelligence to address complex challenges in health and the environment. With contributions from renowned scholars worldwide, this book illuminates recent advances through illustrative figures and case studies that enhance understanding of complex pathways while bioinformatics strategies streamline research outcomes. This book is a must-read for researchers, academics, and professionals in life sciences, biomedical fields, and environmental studies, interested in advancing their knowledge of multi-omics applications. It is also beneficial for scientists involved in drug design or biotechnological innovations related to environmental sustainability.
CRIS-Team Scopus Importer:2025-11-28